The Deficit of Early Selective Attention in Adults With Sluggish Cognitive Tempo: In Comparison With Those With Attention-Deficit/Hyperactivity Disorder - Park, Yelin; Lee, Jang-Han (Frontiers in Psychology, 2021)
Sluggish cognitive tempo (SCT) is a cluster of attentional symptoms characterized by slow information processing and behavior, distractibility, mental confusion, absent-mindedness, and hypoactivity. The present study aimed to compare early and late selective attention in the information processing speed of adults with SCT to those with attention-deficit/hyperactivity disorder (ADHD) and adults without any attentional problems. The participants were screened using Barkley Adult ADHD Rating Scale-IV and divided into the following groups: SCT (N = 24), ADHD (N = 24), and controls (N = 25). All participants completed the irrelevant distractor task measuring early and late selective attention under load condition (low vs. high) and distractor condition (no-distractor vs. distractor). The inefficiency index was calculated by subtracting the reaction time of no-distractor condition of correct trials from the reaction time of distractor condition to control the impact of accuracy. Upon analysis, the SCT group showed a lower efficiency compared to the ADHD group under high load, while the ADHD group showed lower efficiency under low load than high load. This meant that the ADHD group had increased efficiency of selective attention with higher load, while the SCT group had low efficiency of selective attention even under high loads. These results suggest that the symptoms of “slow” or “distracted” in SCT could be attributed to the reduced speed and efficiency of selective attention in early information processing and the problem can be pronounced in situations with distractors. The results of the study imply that the attention-deficit-like symptoms shown in those with SCT and ADHD can be distinguished in specific stage of information processing.